INOVASI PANGAN LOKAL BERBASIS SINGKONG: PEMBERDAYAAN MASYARAKAT DESA DI HALMAHERA UTARA - Alfred Labi; Margaretha Tabita Tuny; Dominggus Isak Bitjara; Ebedly Lewerissa; Kezia Wenno; Davidson Corneles Nusa (PAKEM: Jurnal Pengabdian Kepada Masyarakat, 2026)
The Community Service Program (PKM) aims to empower the community of Kali Upa Village, North Halmahera, through the diversification of cassava into value-added sagu lempeng products. The main problems faced by the partner community include the low market value of cassava, limited knowledge of processing technology, and weak market access. The implementation methods consisted of socialization activities, product diversification training, provision of simple production equipment, business management assistance, digital marketing training, as well as monitoring and evaluation. The results of the program show an increase in production capacity by up to 40%, a reduction in drying time from two days to approximately 5–6 hours, and product innovation in four flavor variants (original, palm sugar, coconut, and chocolate). The partners have also adopted simple financial record-keeping practices and digital marketing strategies through social media, which have expanded market reach and strengthened product branding. This program has contributed to increased household income, women's empowerment, and the strengthening of local food identity. The PKM model can be replicated in other villages with similar potential in order to enhance family economic resilience, particularly among women household artisans producing sagu lempeng in North Halmahera.